Scar endometriosis: a mystery entity - Kankanala, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Scar Endometriosis is described as having an active endometrial tissue at the scar area outside the uterine cavity. Corner stone for diagnosis is proper history, clinical examination and suspicion-based imaging. Caesarean scar endometriosis (CSE) usually seen following procedures like caesarean sections, hysterectomies. Time of presentation can be very variable so yet times difficult to suspect. Once suspected Convincing patient that they have active glands other than in uterine cavity is not easy. Hence proper imaging and biopsy is needed to backup for thorough counselling and treatment to improve the quality of life.